PROFIL PEMAHAMAN KESETARAAN GENDER PADA MAHASISWA FAKULTAS TARBIYAH DAN KEGURUAN UIN ANTASARI BANJARMASIN - Zahidah, Asih Noor; Nuraini, Helma; Istati, Mufida (Jurnal Studi Gender dan Anak, 2023)
Awareness of gender equality is required to achieve a higher quality campus life because every individual gets the same rights and opportunities. The ideal gender equality will improve the quality of education and teaching, including the quality of human resources on campus. This study aims to determine the level of awareness of gender equality of students of the Tarbiyah and Teacher Training Faculty of UIN Antasari Banjarmasin. The research method uses a quantitative descriptive approach. The data collection instrument uses a gender equality awareness questionnaire, covering 2 aspects, first; the concept and role of gender and second; gender inequality awareness. In general, there are 3 categories; students who have a low awareness of gender equality by 8.06%, medium by 86.08%, and high by 5.06%. The level of student understanding of gender roles and concepts is lower than the analysis aspect of gender inequality problems. This is because the concept and role of gender have not been properly internalised, although the understanding of gender inequality can be better understood. Keywords: Profile, Gender Equality Awareness, Student College, FTK UIN Antasari